FEMINISME NOVEL KENANGA KARYA OKA RUSMINI: KAJIAN KERELEVANSIAN DENGAN PEMBELAJARAN BAHASA INDONESIA - Linggar Dyah Satriyani; Suyitno Suyitno; Chafit Ulya (Universitas Sebelas Maret, 2018)
The aims of this research is to describe and to explain: (1) the structure of the novel Kenanga by Oka Rusmini; (2) the form of the gender inequity that happen with the women characteristic in novel Kenanga by Oka Rusmini; (3) the form of the culture rebellion of women characteristic in novel Kenanga by Oka Rusmini; (4) the relevancies of novel Kenanga by Oka Rusmini as bahasa Indonesia teaching materials in SMA. This research is a qualitative descriptive research. Technique of data validity was using triangulation methode. Technique of data analysis was using flow analysis. The result of the study show that: (1) the structure of the novel Kenanga by Oka Rusmini contains theme, plot, figures, setting, and moral value; (2) the form of the gender inequity in novel Kenanga by Oka Rusmini is in the form of determining and choosing women’s life that it is belief not equitable; (3) the form of the culture rebellion by women characteristic in novel Kenanga by Oka Rusmini is the desire to live freely without any rules of the tradition and culture; (5) there is relevance of the novel Kenanga by Oka Rusmini as bahasa Indonesia teaching materials in SMA.